HEALTH CARE ACCESS & EQUITY: ADDRESSING DISPARITIES IN KENYA - Tabitha, Precious (UoEm, 2024)
Health involves thriving into various aspects of life and encompasses more than just avoiding to get sick. It includes various factors such as the mental, physical and social well-being of an individual. It is not just merely one lacking a disease or complications in the body but also just having piece of mind and a stable state of reasoning. By physically being healthy it means that one’s body organs are working optimally and normally and that the person has adequate rest, regular exercise and always has a balanced diet. Mental health is also very essential since it entails emotional stability where one has a sense of purpose and is calm emotionally and thus the famous saying by Elyn R. Saks that ‘No one would ever say that someone with a broken arm or a broken leg is less than a whole person, but people say that or imply that all the time about people with mental illness.’ Social wellbeing revolves around creating relationships, connecting with people and the world. Kenya recently has encountered a tough situation where doctors in the country went on strike for about a month demanding for better payment and proper working conditions which lead to public hospitals being empty and patients having to run to expensive private hospitals to seek medical attention. Such strikes highlight the various issues facing the quality of the Kenyan health system. Despite such health problems Kenya has also been seen to ensure proper health services to its people and one of the ways is that Kenya has joined the International Vaccine Institute as a member state strengthening efforts to ensure access to vaccines and health security. Our very own Court of Appeal has recently approved the Social Health Insurance Fund (SHIF) which is President Ruto’s initiative to address the disparities in health care access and improve health outcomes. Therefore, despite the country facing health quality standards issues there is also a big attempt to ensure good health for its citizens. The Universal Health Coverage also serves as a good mechanism for the betterment of the Kenyan Health System. This paper investigates the state of healthcare in Kenya, focusing on access to quality services, healthcare infrastructure, public health initiatives and efforts to achieve Universal Health Coverage.
Keywords: HEALTH CARE ACCESS & EQUITY; ADDRESSING DISPARITIES IN KENYA